THE EFFECT OF TAX BURDEN, FOREIGN OWNERSHIP, INTANGIBLE ASSETS AND BONUS MECHANISM ON TRANSFER PRICING: (Empirical Study on Mining Sector Companies listed on the IDX 2017-2021) - Nur Hafifah; Chaidir Chaidir Djohar (Transpublika Publisher, 2023)
In Indonesia, a country with a significant mining industry and a dynamic stock exchange, transfer pricing decisions among mining companies have become a subject of interest. These decisions involve determining the prices at which related entities within the same multinational corporation trade with each other. The complexity arises from the potential discrepancies between market prices and the prices set for intra-company transactions. This study aims to investigate the impact of Tax Burden, Foreign Ownership, Intangible Assets, and Bonus Mechanism on Transfer Pricing Decisions among Indonesian mining firms listed on the Stock Exchange from 2017 to 2021. Using purposive sampling, six mining companies were selected as the research sample. Employing Panel Data Regression Analysis via Eviews 9 software at a 5% significance level, the study finds that collectively, the independent variables significantly influence companies' choices for transfer pricing, as indicated by the F-test (F-statistic value = 13.07910, F-table value = 2.759). Regarding individual variables, Tax Burden lacks significant influence (p-value = 0.3819), while Foreign Ownership negatively impacts transfer pricing decisions (p-value = 0.002, t-statistic = -3.503829). Intangible Assets (p-value = 0.8969) and Bonus Mechanism (p-value = 0.6290) also do not significantly influence transfer pricing. The study concludes that investors should cautiously analyze company policies due to varied motivations for transfer pricing, and recommends government review of policies to curb detrimental transfer pricing practices. The limited number of multinational mining companies and scarce information on their transfer pricing practices are study limitations.